Two-Year Outcome From Combining Cryoballoon Ablation and Left Atrial Appendage Closure: CLACBAC Study - Ren, Zhongyuan; Zhang, Jingying; Wang, Songyun; Jia, Peng; Li, Xiang; Zhang, Jun; Guo, Rong; Li, Hailing; Li, Shuang; Yang, Haotian; Zheng, Yixing; Meng, Weilun; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective: Catheter ablation combined with left atrial appendage closure (LAAC) has emerged as a promising strategy for atrial fibrillation (AF) patients at high risk for stroke or with contraindications for oral anticoagulants (OACs). But the evidence for the long-term safety and efficacy of a combined procedure using cryoballoon ablation (CBA) with LAAC is still insufficient. Methods: From October 2015 to December 2017, a total of 76 consecutive non-valvular, drug-refractory AF patients who underwent a combined procedure of CBA and LAAC are included. Peri- and post-procedural safety and efficacy were evaluated through scheduled follow-ups and transesophageal echocardiography (TEE). Results: A total of 74 patients (97.4%) underwent the combined procedure and achieved instant pulmonary vein isolation and satisfactory LAAC. With a mean follow-up time of 23.7 ± 11.0 months, the recurrence of atrial arrhythmia was recorded in 35 patients (48.0%). In addition, a survival analysis shows a non-significant higher recurrence in persistent AF (p = 0.48). The overall OAC withdrawal rate was 97.2%, and one patient (1.4%) had a lethal hemorrhagic stroke while on single antiplatelet therapy. For safety concerns, the overall mortality was 2.7%, which resulted from one case of myocardial infarction on OAC and one hemorrhagic stroke, as mentioned. No other major hemorrhagic events occurred. Among the 72 patients (94.7%) who underwent TEE, one patient (1.4%) had device-related thrombosis and one patient (1.4%) had prominent residual flow (over 3 mm). Both were prescribed long-term OACs without severe complications occurring. Conclusions: Combining CBA with LAAC in a single procedure achieved considerable long-term safety and efficacy, providing a promising strategy for AF management.